Leiden Mutation and the Course of Severe Acute Pancreatitis - A. V. Ershov; V. T Dolgikh; T. I. Dolgikh; S. V. Morozov; Yu. P. Orlov; A. B. Reis (Общая реаниматология)
Objective: to evaluate the impact of Leiden mutation on the course of severe acute pancreatitis. Subjects and methods. One hundred and twelve people were examined. Group 1 comprised 50 patients diagnosed with severe acute pancreatitis without coagulation factor V (Leiden) mutation. Group 2 included 42 patients with severe acute pancreatitis who were found to have Leiden mutation. Acute pancreatitis was first diagnosed in both groups. Group 3 consisted of 20 apparently healthy individuals (a control group). The severity of the underlying disease was determined in accordance with the clinical and laboratory parameters recommended by the I. I. Dzhanelidze Saint Petersburg Research Institute of Emergence Care. Results. This investigation revealed an association of Leiden mutation with trends in the development of acute pancreatitis. Group 2 exhibited a more severe disease: large focal pancreatic necrosis was twice more common and infectious complications developed more frequently; more aggressive and radical treatments were more often used. The patients with Leiden mutation had higher mortality rates (33% in the Leiden mutation group and 24% in the non-mutation group. Conclusion. The findings should be kept in mind in elaborating new diagnostic methods and principles in the treatment of the underlying disease and in the prevention of its complications in patients with severe acute pancreatitis. Key words: acute pancreatitis, Leiden mutation.